Response of soil bacterial community and geochemical parameters to cyclic groundwater‐level oscillations in laboratory columns - Xia, X. (2020)
Results showed that water saturation and O2 level oscillated with groundwater level in NF and RI columns. Total organic C removal rates in RI column were the highest across vadose (∼38.4%), oscillated (∼35.8%), and saturated (∼35.2%) zones. Deltaproteobacteria, which were significantly correlated with TOC removal (p < .05), were found in higher abundance in the vadose and oscillated zones of the RI column than in the QS and NF columns. Soil bacterial community structure was dynamic at the class level due to water saturation, O2 level, and TOC removal. Total organic C removal was the driver to separate the distribution of bacterial community structure in the vadose and oscillated zones of the RI column from those of the QS and NF columns. This study suggests that RI induced rapid, short‐term, cyclic, groundwater‐level oscillations could significantly influence both the soil C cycle and bacterial community structure in the vadose and oscillated zones.